Characteristics of pyramid structure and agency problems among Malaysian firms - Salamudin, Norhana; Ahmad, Noryati; Basir Malan, Irfah Najihah (2012)
A pyramid structure is a business entity such a group of companies whose ownership structure displays a top-down chain of control. According to Attig, Fischer and Gadhoum (2003), a firm is considered as affiliated to pyramidal firms if it is controlled through pyramidal structure and has at least one intermediary firm in its ownership chain. In such a structure, the ultimate owners are located at the apex of the pyramid structure with successive layers of firms below the ultimate owners. Accordingly, the length of layers of pyramidal firms leads to the opportunistic behaviour of ultimate owners to expropriate the minority shareholders' interest. Meanwhile, non pyramidal firm is the existence of one or more firms between the one affiliate and the ultimate owner which has the same voting and cash flow rights compared to pyramidal firm. La Porta, Lopez and Shleifer (1999) document that ultimate owners around the world usually use this pyramid structure to control several firms simultaneously. According to Bunkanwanicha and Wiwattankantang (2008), firms are placed in different layers in the pyramid structure to serve a specific purpose. For example, those firms at the lower layers in the pyramid structure are used to take riskier investment that may create large cash flow but those in the upper layers will be used to absorb the positive outcomes from the successful investment undertaken by the affiliates. A direct result of the pyramid structure is a separation of actual ownership, or cash flow rights, from voting power or control rights, especially firms placed in the lower level of the structure (Claessens, Djankov and Lang, 2000). Cash flow rights represent owner's actual ownership in a company (Claessens, Djankov, Fan and Lang, 2000b). Chapelle and Szafarz (2005) defined control with respect to the majority voting rule where the control ratio of a shareholder is obtained by dividing the share of control he can exercise directly or indirectly over a given company, by the percentage of shares he